Moderating Effects of Striving to Avoid Inferiority on Income and Mental Health - Nagae, Asa; Asano, Kenichi; Kotera, Yasuhiro (Frontiers in Psychology, 2022)
Many people experience feelings of inferiority. The concept of striving to avoid inferiority, which is a belief that effort can overcome inferiority, has been the focus of recent studies. This study examined the effect of striving to avoid inferiority on mental health and well-being. We hypothesized that striving to avoid inferiority would modify the relationship among socioeconomic status, mental health, and well-being, therefore examined the effect of striving to avoid inferiority on the relationship between annual income, mental health, and well-being. The participants were 491 adults (241 men and 250 women). The results indicated that insecure striving (IS) in competition with others positively correlated with depression, anxiety, and stress, whereas secure non-striving (SNS) in acceptance of inferiority positively correlated with the satisfaction with life and negatively correlated with depression. The effect of striving to avoid inferiority on the relationship among annual income, mental health, and well-being indicated that SNS affected the relationships between annual income and well-being, annual income and depression, income and anxiety, and the interaction between IS and SNS. Moreover, the relationship between income and stress was influenced by SNS and the interaction between IS and SNS. These results indicated that SNS or the interaction between IS and SNS were the only variables regulating the relationship among annual income, mental health, and well-being. These findings suggested that accepting feelings of inferiority or striving to avoid inferiority influences the mental health and well-being of people.